Membangun Bisnis Berkelanjutan: Sinergi Keuntungan Finansial, Pemberdayaan Masyarakat, dan Perlindungan Lingkungan menurut Ekonomi Islam - Rizka Fuziana Pangesti; Putra Jaya; Lisnawati (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
his study examines the concept of sustainable business development through the lens of Islamic economics, focusing on the integration of three core dimensions: financial profit (profit), social empowerment (people), and environmental stewardship (planet). The urgency of this research is driven by the global environmental crisis and social inequality, which demand business models that pursue long-term welfare rather than merely short-term gains. Using a qualitative approach through a systematic literature review, this research analyzes how Islamic economic principles—including tawhid, justice ('adl), and the responsibility of khalifah—align with and reinforce the Sustainable Development Goals (SDGs). The findings indicate that the Profit-People-Planet framework is not only compatible with Islamic teachings but is deeply embedded in Islamic economic ethics and the maqashid al-shariah framework. Instruments such as zakat, waqf, and Islamic financing serve as practical mechanisms that simultaneously support halal profit generation, enhance community welfare distributively, and ensure environmental protection through the principle of hifz al-bi’ah. This study concludes that Islamic economics offers a holistic, ethical, and value-based framework for building sustainable businesses that are profitable, socially responsible, and environmentally conscious in the modern era.